Pengaruh jumlah automated teller machine (atm) dan jumlah cabang serta status devisa terhadap profitabilitas - Dela Farah Diba; F. Defung; Doddy Adhimursandi (Fakultas Ekonomi Dan Bisnis Universitas Mulawarman, 2018)
The effect of automated teller machine (ATM), branch and foreign exchange status on profitability at private national bank in Indonesia, supervised by F. Defung and Doddy Adhimursandi. The aim of study is to analyze the effect of ATM, number of branch and foreign exchange status on profitability (Return on Asset/ROA) at private national bank in Indonesia. There are 36 banks included in the data set, covering period of 2012-2015, and multiple regression analysis is used to analyze the data. The result show that number branch have a positive impact and statistically significant on ROA. However the effect of Automated Teller Machine and Foreign Exchange Status indicate that there is a positive but not significant on ROA. Therefore, the hypothesis on the positif effect of ATM and foreign exchange status on bank profitability is rejected